Perception, adoption determinants and challenges of combine harvesting in haor ecosystem: an empirical study on boro rice farming: An empirical study of combine harvesting on boro rice farming - Md Taj Uddin; Shama, Andrila Sarker; Nasrin, Mahmuda; Kundu, Nanda Dulal; Tushar, Md Touhedul Islam (Annals of Bangladesh Agriculture, 2026)
The use of combine harvester is a modern technological solution to current rice production in Bangladesh, especially in haor ecosystem where timely harvesting of paddy is very important for minimizing crop losses due to flash floods. An extensive field survey was conducted to assess the farmers’ perception, adoption drivers and challenges of combine harvesters in three haor districts namely Sunamgonj, Kishorgonj and Netrokona. The field level data were collected from 360 rice growing farmers (239 adopter and 121 non-adopter) since November 2023 to April 2024 using multistage random sampling. A structured questionnaire survey was used for the collection of primary data. Descriptive statistics, the 5-point Likert scale and a binary logistic regression model were applied to achieve the objective of the study. The meeting point for mechanization in harvesting, being 92%, showed that a quicker adoption of technology occurred. Mechanization for harvest was seen by farmers to be beneficial in terms of reduced labor, decreased production costs and time, despite the high initial investment cost and on-going cost of maintaining such equipment. On the other hand, education, group membership, market information, access to credit, training and extension services strongly determined the adoption decision positively whereas, age had negatively significant effect. The major challenges in the study areas, were found to be limited credit facilities (91.0%), low custom hiring availability (88.0%), high machine prices (80.0%) and small fragmented plots (80.0%), respectively. The study also suggests some recommendations like improving credit access, farmers training, extension services and cooperative-based machinery ownership are vital to ensure sustainable mechanization for enhancing farmers’ livelihood in haor ecosystem. Ann. Bangladesh Agric. 29(2): 239-264